1995
DOI: 10.1177/00220345950740021301
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cellular Responses Involved in Reparative Dentinogenesis in Rat Molars

Abstract: During primary dentin formation, differentiating primary odontoblasts secrete an organic matrix, consisting principally of type I collagen and non-collagenous proteins, that is capable of mineralizing at its distal front. In contrast to ameloblasts that form enamel and undergo programmed cell death, primary odontoblasts remain metabolically active in a functional tooth. When dentin is exposed to caries or by operative procedures, and when exposed dentinal tubules are treated with therapeutic dental materials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 28 publications
4
61
0
5
Order By: Relevance
“…Regarding the regenerative process after tooth injuries such as cavity preparation and pulpal capping following pulp exposure, newly differentiated or surviving odontoblast-like cells express Dsp protein in addition to the immunoreaction in the tertiary dentin (14,25), suggesting that this protein is a reliable marker for regenerated odontoblasts and tertiary dentin. However, immunohistochemistry for Dsp is unable to determine the up-regulation of Dsp production in the afflicted odontoblasts, because Dsp protein has already been accumulated in their cytoplasm.…”
Section: Molar At Week 3 (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the regenerative process after tooth injuries such as cavity preparation and pulpal capping following pulp exposure, newly differentiated or surviving odontoblast-like cells express Dsp protein in addition to the immunoreaction in the tertiary dentin (14,25), suggesting that this protein is a reliable marker for regenerated odontoblasts and tertiary dentin. However, immunohistochemistry for Dsp is unable to determine the up-regulation of Dsp production in the afflicted odontoblasts, because Dsp protein has already been accumulated in their cytoplasm.…”
Section: Molar At Week 3 (Table 2)mentioning
confidence: 99%
“…The expression of Dsp mRNA in the odontoblasts became weak in intensity at Week 5 and almost disappeared at Week 8 in this study, suggesting the existence of odontoblasts that have vacated an active synthetic phase and committed to a quiescent phase. The term "resting odontoblasts" seems suitable for the definition of these cells (13,14).…”
Section: Classification Of Odontoblast-lineage Cells (Table 3)mentioning
confidence: 99%
“…23,24 ALP and OCN are initial-stage and late-stage markers of osteogenic differentiation, respectively. 25 These molecules are considered crucial markers for dentinogenesis Figure 4 analyses of mrNa expression of human dental pulp cells by quantitative real-time Pcr.…”
mentioning
confidence: 99%
“…A striking feature of the comparison between primary odontoblast and odontoblast-like cell differentiation is the absence of involvement of dental epithelium in the latter situation 26) . Despite of this critical importance, parallel molecular mechanisms may exist between dental repair and morphogenesis in the embryo, as suggested that some molecular mechanisms are common to dental development and repair 27) .…”
Section: Discussionmentioning
confidence: 99%